Glial Activation in the Thalamus Contributes to Vestibulomotor Deficits Following Blast-Induced Neurotrauma - Dickerson, Michelle R.; Bailey, Zachary Stephen; Murphy, Susan F.; Urban, Michael J.; VandeVord, Pamela J. (Frontiers in Neurology, 2020)
Vestibular impairment has become a frequent consequence following blast-related traumatic brain injury (bTBI) in military personnel and Veterans. Behavioral outcomes such as depression, fear and anxiety are also common comorbidities of bTBI. In order to accelerate pre-clinical research and therapy developments, there is a need to study the link between behavioral patterns and neuropathology. The transmission of neurosensory information often involves a pathway from the cerebral cortex to the thalamus, and the thalamus serves crucial integrative functions within vestibular processing. Pathways from the thalamus also connect with the amygdala, suggesting thalamic and amygdalar contributions to anxiolytic behavior. Here we used behavioral assays and immunohistochemistry to determine the sub-acute and early chronic effects of repeated blast exposure on the thalamic and amygdala nuclei. Behavioral results indicated vestibulomotor deficits at one and three weeks following repeated blast events. Anxiety-like behavior assessments depicted trending increases in the blast group. Robust levels of astrogliosis and microglia activation were observed upon post-mortem pathological examination in the thalamic region, however, a limited glia response was found in the amygdala at four weeks. These findings are consistent with a diffuse glia response associated with bTBI and support the premise that dysfunction within the thalamic nuclei following repeated blast exposures contribute to vestibulomotor impairment.